A histomorphological and immunohistochemical study on the lactotrophs in pars distalis adenohypophysis of buffalo - KHAN, MASSARAT; SAIGAL, R P; SETHI, R S (The Indian Journal of Animal Sciences, 2013)
In order to localize and characterize the lactotrophs in hypophysis cerebri of 53 buffalo of either sex of varying age were used. The lactotrophs were round, irregularly polygonal or rarely elongated in shape. The average diameter of these cells was 7.6 to 8.0 um in males up to 4 months of age, and 9.8 um in adult males and in female during follicular phase. These cells were larger in luteal phase and in pregnancy. The regional variations in the size of the lactotrophs evidenced the smallest cells in zona luberalis (8.8 um) and the largest in the ventral region (9.6 um). Of the chromophils the lactotrophs were distributed in maximum proportions (29.46%) in the ventral uspects of the pars distalis and minimum in the central region and zona tuberalis. In males, the lactotrophs constituted 15.48% of the chromophils in one week calves, decreased to 8.68% by 4 months, whereafter increased to 14.08% in adults. The lactotrophs were in higher proportions in cyclic/pregnant females. They decreased during carly pregnancy (18.76%) and were in largest in later stage of pregnancy (27.60%).